A Holistic Integrated Intellectual Capital Ecosystem Model for Enhancing the Sustainability of Malaysian SMEs: A Conceptual Study - Hashim, Maryam Jameelah Mohd; Hanefar, Shamsiah Banu Mohamad; Mohammad, Suleiman Shlash; Khamis, Mohd Rahim; Vasudevan, Asokan; Osman, Idris; Ozturk, Ilknur; Hanami, Zarah Arwieny (International Review of Management and Marketing, 2026)
Small and medium enterprises (SMEs) play a critical role in driving economic growth, employment, and innovation, particularly in emerging economies such as Malaysia. Despite their contributions, many SMEs struggle to achieve long-term sustainability due to resource constraints, technological disruption, and increasing competitive pressures. Intellectual capital (IC) has been widely recognised as a strategic intangible resource that enhances innovation capability, operational efficiency, and competitive advantage. However, conventional IC frameworks, typically limited to human, structural, and relational capital, may not sufficiently capture the broader range of intangible resources required in today’s complex business environment. This conceptual study proposes a Holistic Integrated Intellectual Capital Ecosystem (IICE) model that extends traditional IC frameworks by incorporating six key dimensions: human capital, structural capital, customer capital, technological capital, social capital, and spiritual capital. The model further introduces leadership as a moderating capability that influences the effectiveness of intellectual capital in enhancing SME sustainability. Drawing on Intellectual Capital Theory, Resource-Based View, and sustainability leadership perspectives, this study develops an integrated conceptual framework explaining how interconnected intangible resources contribute to organizational resilience and sustainable performance. The proposed model advances the intellectual capital literature by offering an ecosystem-based perspective that integrates knowledge resources, technological capabilities, relational networks, and ethical values within a leadership-driven sustainability context. The study provides practical implications for SME managers and policymakers by emphasising the importance of leadership development, enhancing digital capabilities, and fostering stakeholder collaboration. It also provides a foundation for future empirical research examining the relationships among intellectual capital components, leadership practices, and sustainable performance in SMEs.